Which education model for the Armed Forces and National Security to choose – can Croatia learn from Portugal? - Novak, N.; Silva, T. D. H. (Strategos: Scientific journal of the Croatian Defence Academy, 2018)
This paper seeks to answer whether the concept development of education for the Croatian Armed Forces and national security may learn from Portuguese experience. By doing so, it reviewed theoretical notions of defence and security studies, contemporary concepts in education for the armed forces and national security, and it offered a case study of Portugal in this field. The current objectives of the national security in Croatia, as defined in National Security Strategy 2017, point towards the need of establishing an adequate education system, at the state level. The paper offers contemporary Portuguese experience as a potential example for implementation in Croatia.